LAPORAN ARUS KAS: SEJARAH PERKEMBANGAN PENGGUNAAN METODE LANGSUNG DAN TIDAK LANGSUNG - Purbandari, Theresia (Widya Warta, 2009)
Cash flow statement of a company is very helpful for financial statement users as basis to evaluate the ability of the company in producing cash and cash equivalent, as well as to evaluate the need of the company to use the cash flow intended. Cash flow statement is classified on the basis of operation, investment, and financing activities. Indonesian Institute of Accountants (IAI, 2002: 18) suggested companies to report their cash flow of operation activity by using direct method. This method produces information useful in estimating future cash flow which can not be produced by the use of indirect method. This research aimed to analyze the development history of the use of direct and indirect methods. The data used were the manufacture companies firstly listed at Jakarta Stock Exchange (JSX) up to the year 1994 and still listed at JSX up to the year 2007, and on 18 April 2009 the companies were recorded at business and finance data of Kompas. The sampling criteria, therefore, resulted 66 companies as sample. The result of analysis showed that since the year 1995 up to the year 1998 the entire company sample applied indirect method. In the year 1999 the companies began to make use of direct method. Hence, from the year 2001 up to Â the year 2007 all company sample used direct method. This fact indicated that there was usage development of direct and indirect methods in operation activity of cash flow reporting. It also showed that the companies were loyal towards Statements of Â Financial Accounting Standards (SFAS) No. 2 year 2002 paragraph 18.